INTERNALIZATION OF BALINESE LOCAL WISDOM THROUGH STORYTELLING IN EARLY CHILDHOOD EDUCATION - Suci, I Gede Sedana; Ubaidillah, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the development of moral values through Balinese folklore. This study was conducted on children aged 5-6 years. The type and approach used are qualitative discriptive. Data analysis uses interactive descriptive analysis models such as data reduction, presentation, verification, and conclusion. Test the validity of the data using triangulation techniques. The results showed that there are several stories of local wisdom of Balinese people can be used as examples of moral values in children through the attitudes of characters in Balinese folklore. Exemplary behavior such as being honest, helpful, courteous, respectful, can distinguish good and bad attitudes.